Outbreak of Pan-resistant Acinetobacter Species in Intensive Care Units of a tertiary care hospital - Kiran Fatima, Kiran Ahmad, Asma Ejaz, Nazia Mir, Saadia Ch (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Acinetobacter has gained significant importance in the medical literature due to the steady development of drug resistance since1980s. Aim: To investigate various patterns and susceptibility trends of the Acinetobacter bacteria isolated from the patients of Intensive Care Units in Holy Family Hospital, Rawalpindi. Methods: It was a cross sectional study carried out at Holy Family Hospital, Rawalpindi from January-July 2019 including case data from intensive care units of medical, surgical, burn and pediatric departments. Acinetobacter isolates were cultured from intensive care units. Antibiotic susceptibility testing was performed using disc diffusion method. Atotal 204 cases of Acinetobacter infection were isolated, of these 102 isolates were from intensive care unit. Majority of the cases were males (56.9%). Results: Our results validate that intensive care units are the main source of overall hospital acquired infections such as Acinetobacter baumanni as half of our cases were isolated in ICUs compared to half in all other general departments. Acinetobacterwas the most common bacterial pathogen 141 (69.1%) isolated in this study followed by klebsiella spp. 32 (15.7%) and e-coli 15 (7.4%). Acinobacter was found to be pan-resistant in more than 80% of the cases. Campylobacter showed frequent resistance to the drug TZP (85%) followed by CAZ (67.6%), SCF (66.2%) and CRO (60.3%). Conclusion: Pan-resistance to Acinetobacter can be associated to the misuse of antibiotics and environmental contamination of hospital equipment and hence it can be implied that these factors play a major role in the outbreaks of Acinetobacter spp.